A base isolation system for bridges subjected to seismic disturbances. - Kaplan, H. (Earthquake engineering & structural dynamics.)
The study reported in this paper investigates the feasibility of developing an active base isolation system for the protection of bridges subjected to earthquakes. The proposed system incorporates spherical supports, cams and springs which can be optimally designed to minimize the transmissibility of the seismic disturbances to the bridge. The considered example shows that the proposed design is implementable and can provide an order of magnitude reduction in the maximum stress resulting from seismic waves acting on the bridge in the transverse or longitudinal direction. Since the system performance is highly dependent on the rapid unlocking of the cams in the event of a seismic disturbance, careful consideration should be given to the design of a reliable cam release control. This can be achieved by spring loading each cam such that it would be normally unlocked. A hydraulic actuator would be used to force it to rotate to the locking position under fluid pressure which would be constantly maintained at the design level during normal conditions. The actuator would be equipped with a quick response release valve for rapidly releasing the pressure and consequently unlocking the cam as soon as an earthquake is detected.